Magnetic Gelatin Microspheres for Targeted Release of Doxorubicin - Josefa Virginia da Silva Souza; Manoel Ribeiro da Silva; Marcos Antonio da Silva Costa (Materials Research, 2021)
The aims of this work were to develop a magnetic carrier system consisting of microspheres made of gelatin for controlled release of doxorubicin and to investigate the ability of fructose, glucose, genipin and 1-ethyl-3(3-dimethylaminopropyl)carbodiimide (EDC) as crosslinking agents of gelatin microspheres. In addition, we also investigated the changes in the microspheres’ magnetic properties produced by using magnetite incorporated by three different methods and the doxorubicin release performance by using a constant, oscillating or no external magnetic field. The system obtained with fructose as crosslinker (low toxicity) was superparamagnetic, with high saturation magnetization and release profiles that could be controlled. Among the crosslinkers studied, genipin was the most efficient to reduce the solubility of the gelatin microspheres in water. When ferrous chloride was employed in magnetite synthesis, the Ms showed the highest values (61.6 emu/g), and its use in magnetic gelatin microspheres allowed the production of systems with high magnetization (29.6 emu/g).